Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the Conference on Design, Automation and Test in Europe 2008
DOI: 10.1145/1403375.1403694
|View full text |Cite
|
Sign up to set email alerts
|

Emerging yield and reliability challenges in nanometer CMOS technologies

Abstract: With further scaling of nanometer CMOS technologies, yield and reliability become an increasing challenge. This paper reviews the most important phenomena affecting yield and reliability. For each effect, the basic physical mechanisms causing the effect and its impact on transistor parameters are described. Possible solutions to cope/handle with these effects on the design level are discussed as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 36 publications
0
50
0
Order By: Relevance
“…Recent work has shown that the threshold voltage shift as a function of time under DC stress (t DC ) is best modeled with the trapping/de-trapping theory [3][4][5][6]:…”
Section: Nbti/pbtimentioning
confidence: 99%
“…Recent work has shown that the threshold voltage shift as a function of time under DC stress (t DC ) is best modeled with the trapping/de-trapping theory [3][4][5][6]:…”
Section: Nbti/pbtimentioning
confidence: 99%
“…Time-dependent degradation Time-dependent degradation effects will cause a change of the transistor parameters (V T , J, r o ) as a function of time and therefore might turn an initially fully functional circuit into a less or even non-functional circuit over time [2]. This degradation depends on the stress applied to the device, i.e.…”
Section: 2mentioning
confidence: 99%
“…Both NBTI and HC increase exponentially with the stress voltage [2]. Therefore, the effect of time-varying stress signals must be included in the model to assure a sufficiently accurate degradation calculation.…”
Section: Degradation Modelsmentioning
confidence: 99%
“…According to the ITRS roadmap both analog and digital ICs start to suffer from die-level reliability phenomena, e.g. Negative Bias Temperature Instability (NBTI) and Hot Carrier degradation (HC) [1], [2]. Statistical circuit analysis through accelerated stress testing (i.e.…”
Section: Introductionmentioning
confidence: 99%